A instituição e a majoração de tributos através de medida provisória - Chaves, Éder Sandro Lima (Universidade Federal do Tocantins, 2022)
The present work was elaborated with the intention of making an analysis, although without intending to exhaust the subject, on the use of the institute of the provisional measure in tax matters, particularly with regard to the institution and the increase of taxes. It was sought, through bibliographical, empirical, exploratory and qualitative research, using the dialectical method, to make a relationship between such use and some guiding principles of our Democratic Rule of Law, such as the separation of powers, legal security and the legality and its natural consequences in the tax area, especially the principles of tax anticipation and tax legality. For the healthy development of the work, exhaustive research was carried out in the works of some of the most significant authors of the tax doctrine who focused on the subject. Thus, the conclusions reached are based on doctrinal lessons, as it is understood that the scholars are the most knowledgeable on the subject, issuing their opinions from studies and held autonomous and independent reflections, without the influence of external pressures, as is often the case with jurisprudence. In the end, based on the teachings studied, it was concluded that the use of provisional measure for the institution and increase of taxes was illegitimate.